2014
DOI: 10.1097/sla.0000000000000407
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Postoperative Complications on Long-term Quality of Life After Curative Colorectal Cancer Surgery

Abstract: Postoperative complications have adverse effects on long-term QoL, particularly for Physical, Role and Social Functioning, and Body Image, as well as for Mobility, Self-care, and Pain/Discomfort. These findings should inform future preoperative counseling and health care planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
110
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(116 citation statements)
references
References 25 publications
4
110
0
2
Order By: Relevance
“…Anastomotic leak after colorectal surgery increases postoperative morbidity, mortality, length of hospital stay, and nosocomial infection rates, and decreases quality of life (18,25,26). Moreover, anastomotic leak after colorectal cancer surgery may result in poor functional and oncological outcomes (27).…”
Section: Discussionmentioning
confidence: 99%
“…Anastomotic leak after colorectal surgery increases postoperative morbidity, mortality, length of hospital stay, and nosocomial infection rates, and decreases quality of life (18,25,26). Moreover, anastomotic leak after colorectal cancer surgery may result in poor functional and oncological outcomes (27).…”
Section: Discussionmentioning
confidence: 99%
“…However, Brown et al have shown adverse effects in long-term quality of life in patients with postoperative complications. [14] From this aspect, it has come to our attention that short-term outcomes of laparoscopic colorectal surgery are probably better from open surgery, but the outcomes of patients with conversion are less favorable. Designed as a case-controlled study, same number of patients in both groups were included into the study.…”
Section: Discussionmentioning
confidence: 99%
“…Thus disability has been assessed in several studies of cancer patients. 3,8 Recently, Khoei et al 32 proved that the Katz index is a reliable instrument for oncologic patients using the Physical Function subscale of SF 36 as criterion of validity (Cronbach's alpha 0.923).…”
Section: Discussionmentioning
confidence: 99%
“…3, 8 The present study has several shortcomings. First, ADL and HRQoL were not compared before and after surgery.…”
mentioning
confidence: 93%